OVERVIEW OF HIGH RISE DEVELOPMENT IN SURABAYA CITY IN SEVERAL PERIODS OF YEARS - Kartowidjojo, Ribka Irena; Dharmatanna, Stephanus Wirawan (ALUR :Jurnal Arsitektur, 2025)
Surabaya as a metropolitan city, in this era is facing high business activities, economy, education, entertainment and residential needs. The presence of high rise supported by construction technology such as materials or structures, is a solution and opportunity for architecture to answer problems in urban areas by creating buildings that are comfortable and safe for residents and the environment. Starting with the establishment of Wisma BII in 1992 as the first high rise milestone, Surabaya continues to experience rapid development in high rise development. In this research there are 83 high rise buildings in Surabaya that will be analyzed by comparing the main parameters such as function, form, and material. It was found that most of the high rises developed into a mixed use with a setback form and the main structural material is concrete. The analysis was conducted using data from journals and the Council on Tall Building and Urban Habitat (CTBUH) and produced relevant findings. This research is expected to be useful for architects and urban developers in supporting sustainable development in Surabaya.